Comparisons of SME loan performance between BRAC Bank Limited And Southeast Bank Limited - Emon, Ishtiaque Sikder (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.